Production and purification of streptavidin with higher biotin-binding activity - Simson Tarigan; Sumarningsih . . (Indonesian Center for Animal Research and Development (ICARD), 2014)
The objective of this study was to develop practical, efficient method for production, purification and assay of binding activity of streptavidin. Streptomyces avidinii was first propagated on agar plates, the bacterial cells on the agar were scrapped and suspended in a defined synthetic media (4.4 ml/cm2). After 7 days agitation on a rotary shaker (200 rpm/min) at room temprature (≈28°C), the bacterial cells in the culture were pelleted. The culture supernatant was concentrated to 1/62 original volume with 75% saturation ammonium sulphate. After intensive dialysis against ammonium carbonate buffer pH 11, the suspension was loaded into an iminobiotin agarose column chromatography. The adsorbed protein (streptavidin) was eluted with sodium acetate buffer, pH 4, and the eluate was concentrated with an ultrafiltration divice and suspended in PBS. The strepatavidin-binding activity was assayed by a competitive ELISA, a competition between streptavidin in the sample and the HRP-streptavidin conjugate for the biotin (biotinyl IgG) immobilised on wells of a microtitre plate. The detection limit of this assay measured 0.16 µg/ml streptavidin. The method developed in this study produced 160 µg/ml streptavidin in the culture supernatant. After concentration with the ammonium sulphate, the streptavidin concentration increased to 4 mg/ml (69% recovery). At the final step of purification, streptavidin with 10 mg/ml concentration was obtained. The purity of the streptavidin was higher (95%) with a recovary of 19%. The purified streptavidin in this study appeared as a dimer core streotavidin on SDS PAGE and its binding activity was twice as high as that of a commercial one.